Parking structures : construction and design manual - Irmscher, Ilja (Construction and design manual., 2013)
V. 1. Planning principles / introduction by Ansgar Oswald : Car parks: an integral part of the modern history of architecture : How the automobile shapes architecture and urban design ; Ten examples from a hundred-year construction history -- Basic principles of car park planning : Functional architecture for the interplay between cars and their drivers ; The automobile and its driving geometry ; Objective and subjective user requirements ; Requirements for economic operation ; Typical municipal requirements ; Regulations, recommendations and certificates -- Choosing a location: basic decisions : Traffic planning perspectives and economic perspectives ; Urban development issues ; Dimensioning ; Traffic integration -- Car parks as holistic systems : Design philosophy ; Internal traffic functionality ; Car park types ; Parking streets as basic design elements ; Ramps as basic design elements ; Multi-storey car parks -- Further technical features of car parks : Entry and exit drives ; Parking management systems ; Driving lanes and parking spaces ; Walkways and route guidance systems ; Driving surfaces and driving surface markings ; Planning interior heights: special aspects to consider ; Drainage ; Lighting ; Ventilation and smoke extraction ; Carbon monoxide and smoke alarm systems ; Further building services aspects ; Facades and safety barriers ; High-quality interiors -- Mechanical parking systems : Introduction ; Parking lifts ; Sliding pallets ; Turntables ; Car lifts ; Other mechanical parking aids ; Semi-automated parking systems -- Automated parking systems : Introduction ; Mode of operation ; Area and space requirements ; Permissible vehicle dimensions ; Space tolerances and minimum distances ; Stacking principles ; Main types of automated parking systems ; Load lifting systems ; Planning automated parking systems ; Operation and services ; Innovative application -- ... Appendix : Model car park ordinance ; Model inspection ordinance ; Important reference values from the car park ordinances of the German Federal States -- V. 2. Buildings and projects : Freestanding multistorey car parks : Car parks at Klinikum Kassel, Germany ; Gottlieb-Daimler-Stadion, Stuttgart, Germany ; Pressehaus multistorey car park, Bremen, Germany ; Wüste multistorey car park, Lemgo, Germany ; Bollwerksturm car park, Heilbronn, Germany ; Zoo car park, Leipzig, Germany ; Burda company car park, Offenburg, Germany ; Boehringer company car park, Vienna, Austria ; Hallen am Borsigturm car park, Berlin, Germany ; Engelenschanze car park, Münster, Germany ; Ballpark District, San Diego, USA ; Company campus car park, Coesfeld-Lette, Germany ; Neue Messe, Stuttgart, Germany ; Airport car parks P2/P4, Stuttgart, Germany ; Airport car parks P2/P3, Cologne/Bonn, Germany ; Airport car park, Vienna, Austria -- Self-contained underground car parks : Unter dem Altmarkt underground car park, Dresden, Germany ; Coselpalais underground car park, Dresden, Germany ; Kurhaus/Casino underground car park, Wiesbaden, Germany ; Centre Le Flon underground car park, Lausanne, Switzerland ; Laakhaven underground car park, The Hague, the Netherlands ; Hansering underground car park, Halle/Saale, Germany ; Bebelplatz underground car park, Berlin, Germany -- Integrated underground car parks : Oberanger underground car park, Munich, Germany ; Prenzlauer Garden underground car park, Berlin, Germany ; MyZeil/PalaisQuartier, Frankfurt, Germany ; Koepoort underground car park, Delft, the Netherlands -- Small garages : Zapf prefabricated garages ; Integral garage, Los Angeles, USA ; Small integral garage, Nikolina Gora, Moscow, Russia ; Integral garages, Chelobityevo, Russia ; Integral carport, Marbletown, NY -- Automated parking systems : Automated underground car park for residents, Munich, Germany ; Stadtlagerhaus, Hamburg, Germany ;... Messmer-Haus multistorey car park, Frankfurt, Germany ; Fachverband SHK underground car park, Düsseldorf, Germany ; Franklin multistorey car park, Dresden, Germany ; Hauptstresse multistorey car park, Dresden, Germany -- Semi-automatic parking systems : The Blu underground car park, San Francisco, USA ; Kreissparkasse Miesbach car park, Waakirchen, Germany ; Paiais Leopold car park, Munich, Germany -- Mechanical parking systems : Mitterweg 39 car park, Stockdorf, Germany ; Underfloor garage, Via Mateotti, Crema, Italy ; Paul-Lincke-Höfe, Berlin, Germany ; Armenian Church garage, Jaffa, Israel.